Islam and Morality: The Teachings of Al-Ihsan from the Qur'an and Hadith and its Effects on Muslim Ummah - Umar Abdullahi Maidugu; Aliyu Ahmad Abubakar Sadeeq (Walidem Institute and Publishing (WIP), 2024)
This study explores the Al-Ihsan (excellence) concept in Islam, as taught in the Qur'an and Hadith, and its impact on the Muslim community (Ummah). Al-Ihsan is a fundamental aspect of Islamic morality, emphasizing the pursuit of excellence in all aspects of life. Through a critical analysis of Islamic scriptures and scholarly interpretations, this research examines the principles and practices of Al-Ihsan, including its relationship with faith, compassion, justice, and personal development. The study also investigates the effects of Al-Ihsan on the Muslim Ummah, including its role in shaping individual and collective behaviour, promoting social justice, and fostering a sense of community and solidarity. The findings highlight the relevance of Al-Ihsan in contemporary contexts, offering guidance on ethical issues and challenges. This research contributes to a deeper understanding of Islamic ethics and morality, providing valuable insights for Muslims and non-Muslims alike. The research methodology includes a comprehensive review of relevant Qur'anic verses, Hadith, and scholarly works. The study finds that Al-Ihsan has a profound impact on the Muslim Ummah, inspiring individuals to strive for moral excellence, compassion, and justice. The research concludes by highlighting the significance of Al-Ihsan in Islam and its potential to promote a more just, compassionate, and equitable society.